Heat Shock Proteins and HSF1 in Cancer - Cyran, Anna M.; Zhitkovich, Anatoly (Frontiers in Oncology, 2022)
Fitness of cells is dependent on protein homeostasis which is maintained by cooperative activities of protein chaperones and proteolytic machinery. Upon encountering protein-damaging conditions, cells activate the heat-shock response (HSR) which involves HSF1-mediated transcriptional upregulation of a group of chaperones – the heat shock proteins (HSPs). Cancer cells experience high levels of proteotoxic stress due to the production of mutated proteins, aneuploidy-induced excess of components of multiprotein complexes, increased translation rates, and dysregulated metabolism. To cope with this chronic state of proteotoxic stress, cancers almost invariably upregulate major components of HSR, including HSF1 and individual HSPs. Some oncogenic programs show dependence or coupling with a particular HSR factor (such as frequent coamplification of HSF1 and MYC genes). Elevated levels of HSPs and HSF1 are typically associated with drug resistance and poor clinical outcomes in various malignancies. The non-oncogene dependence (“addiction”) on protein quality controls represents a pancancer target in treating human malignancies, offering a potential to enhance efficacy of standard and targeted chemotherapy and immune checkpoint inhibitors. In cancers with specific dependencies, HSR components can serve as alternative targets to poorly druggable oncogenic drivers.